Desenvolvimento de pó de extrato de frutos verdes de aceroleira com elevado potencial antioxidante - Silveira, Amanda Germano (2020)
Acerola is a tropical fruit that has a highest number of bioactive compounds that vary mainly according to its genetics and maturation stage. The objective of this study was to identify which compounds are possibly related to the antioxidant activity of green acerola fruits, and from the most promising clone to obtain these phytochemicals, to study the best extraction conditions for these compounds, and then to perform the drying of the optimized extract using different drying aids, in order to obtain a powder with a high antioxidant capacity that has the possibility of being used as an additive or raw material for the preparation of foods, medicines and / or cosmetics. For this, fruits were harvested at the green maturation stage of four clones of aceroleira, BRS 235 (Apodi), BRS 236 (Cherry), BRS 237 (Roxinha), BRS 238 (Frutacor) that were evaluated for vitamin C content, total polyphenols and antioxidant activity (ABTS and FRAP) and their chemical profile was determined by UPLC-QTOF-MS, and from the data obtained, a chemometric analysis was performed. Phenolic extraction conditions were studied, based on response surface methodology (MSR) using ethanol concentration (%) in the extraction solution and the time of exposure to ultrasound (minutes) as independent variables and the response content of total polyphenols. Drying of the extract obtained under optimal conditions was carried out by lyophilization, using maltodextrin, gum arabic and pectin as drying aids in different proportions, Formulation 1 (F1): 100% maltodextrin, Formulation 2 (F2): 98% maltodextrin + 2% pectin, Formulation 3 (F3): 50% maltodextrin + 50% gum arabic and Formulation 4 (F4): 48% maltodextrin + 50% arabic gum + 2% pectin. According to the chemical profile obtained from the four studied clones, twenty-four bioactive compounds were tentatively identified, and the fruits of the BRS 236 clone had higher ascorbic acid content and its isomer, citric acid, procyanidin B trimer, rutin and higher contents of total vitamin C, total polyphenols and antioxidant activity (ABTS AND FRAP). This study showed that the high contents of ascorbic acid and its isomer, citric acid, procyanidin B trimer and rutin are strongly associated with the antioxidant capacity of green acerola fruits. The fruits of the BRS 236 clone have significantly higher values of these compounds and antioxidant activity, which contributes to its high antioxidant potential. The best conditions for extracting phenolic compounds from green acerolas were achieved when combined hydroalcoholic solution (49.07% ethanol) with a time of exposure to ultrasound of 14.55 minutes. Maltodextrin combined with gum arabic provided greater retention of phenolic compounds, although all formulations studied showed high solubility and antioxidant capacity indicating that they can possibly be used as a raw material rich in bioactive compounds.